Exercise-Induced Increase in Progesterone does not Change FVC and FEV Values in Non Asthmatic Individuals - Messan, Folly; Donouvi, Jéronime; LAWANI, MOHAMED MANSOUROU (My University, 2019)
Background: Progesterone hormone levels increase as a result of different exercise modalities in non-menopausal sportswomen. Progesterone is also involved in dilating the airways when exercise-induced bronchospasm (EIB) occurs in sensitive women. Objective: To determine the effect of elevated exercise-induced progesterone levels on the respiratory airways of non-EIB-susceptible women. Methods: Eleven pre-menopausal girls were recruited. During the luteal phase of their menstrual cycles, blood and respiratory explorations were performed before and after undergoing a comprehensive stress test performed on a cycle ergometer. Progesterone was assayed, and FVC and FEV were determined. Results: The average value of serum progesterone observed after exercise (74.866 ± 24.68 Nmol / L) was significantly (p < 0.05) higher than that recorded (66.072 ± 24.33 Nmol / L) before exercise. The average values of FVC (2.20 ± 0.5 L) and FEV1 (1.90 ± 0.4 L) observed before exercise and those recorded after exercise (2.10 ± 0.6 and 2.10 ± 0.8, respectively), did not significantly differ (p > 0.5). Conclusion: Progesterone, a bronchodilator hormone, does not influence the respiratory airway in subjects that are not sensitive to bronchospasm, even though the stress test induces a high level of this hormone.
Keywords: Menstrual cycle; Progesterone; FEV; FVC; bronchospasm; Stress test